2023
DOI: 10.1007/s12011-023-03558-7
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Characteristics, Source Identification, and Health Risk of Heavy Metals in the Soil-Vegetable System in Two Districts of Bangladesh

Abstract: The consequences of climate change, food security, and self-sufficiency goals are driving excessive human activity onto vegetable farms in Bangladesh, and harmful heavy metal exposure is spreading. So, the study assessed the toxic metals (Pb, Cd, and Cr) exposure, characteristics, and human health risk regarding the soil-vegetable system of two distinct locations in Bangladesh using atomic absorption spectrometry. The average concentration of metals in soil and fertilizer/pesticide samples followed the same or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…Following the criteria set by the USEPA, the non-carcinogenic risk to the health of consumers is not a concern, as the HI value for different veggies, grains, and bread is lower than one [44] . Since every veggie studied in Qureshi et al's research had levels of HMs below acceptable levels, the low absorption of HMs by veggies in this study indicates that the risks to human health are the minimum [45] . Furthermore, Woldetsadik et al's study showed that all types of vegetables had HM levels that were lower than the acceptable limits.…”
Section: Resultsmentioning
confidence: 57%
“…Following the criteria set by the USEPA, the non-carcinogenic risk to the health of consumers is not a concern, as the HI value for different veggies, grains, and bread is lower than one [44] . Since every veggie studied in Qureshi et al's research had levels of HMs below acceptable levels, the low absorption of HMs by veggies in this study indicates that the risks to human health are the minimum [45] . Furthermore, Woldetsadik et al's study showed that all types of vegetables had HM levels that were lower than the acceptable limits.…”
Section: Resultsmentioning
confidence: 57%
“…The estimated daily intake (EDI) of the risk elements was calculated using Eq. (4) [65] , [66] : where: C tuber is the concentration of metals in native potatoes (mg kg −1 ); is the conversion factor (0.085) for fresh vegetables to dry weight [66] ; represents the average daily consumption rate of native potatoes in the highland areas (0.15 kg day −1 for children and 0.45 kg day −1 for adults) [67] ; is the exposure frequency (365 days per year); is the duration of exposure (70 years for adults and 6 years for children) [68] ; is the average body weight (18 kg for children and 64 kg for adults) [67] ; is the average time for non-cancer risks (365 days × ).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…determine the additive and/or interaction impacts of two or more pollutants, the cumulative health risk was calculated by adding the THQ values of each metal and expressing the total THQ (TTHQ) as follows [24]: 5…”
Section: Potential Nutritional and Dietary Intake Contributionsmentioning
confidence: 99%
“…The potential carcinogenic risk of lead, cadmium, chromium, and arsenic exposure in children and adults in the male and female categories was computed as follows [24]:…”
Section: Potential Nutritional and Dietary Intake Contributionsmentioning
confidence: 99%